Realistic simulation in the training of nursing professionals in a vaccination room (Research, Society and Development, 2021)
This study sought to describe the development of a realistic simulation scenario for training nursing professionals in vaccination rooms. This is a qualitative study conducted in vaccination rooms of primary care units of a municipality located in the Western Macroregion of Minas Gerais, between 2018 and 2019. Six nurses and six nursing technicians, as well as five researchers and five graduate students participated in the simulation.. The realistic simulation included three stages: 1) Pre-simulation; 2) Simulation and 3) Debriefing. Content Analysis was used to analyze the data. The participants of the training assumed that the realistic simulation is an innovative methodology, participatory, and very close to the reality of everyday life, and represents a better understanding and reflection on the techniques and routines of immunization services. Realistic simulation is a learning methodology that brings participants closer to their reality. This fact can facilitate a greater appropriation of knowledge, improve the skills of the practices in vaccination rooms.